The Architecture of Nanoparticle Surfaces and Interfaces - Raine, E (2018)
Heterogeneous catalysts are vital for many industrial processes, however the high compositions of platinum group metals mean that the catalysts are often expensive and are not always cost efficient. In many cases, although platinum is a good catalyst, an enhancement in activity can be seen when alloying with a secondary metal. In order to increase the cost efficiency of these catalysts, an improvement in activity and reduction in expensive metal mass is needed. One method of combining these factors is the production of core-shell nanoparticles, removing the highly expensive metal from the inactive particle core while maintaining the close contact of the active metal with the secondary metal. This thesis provides an insight into two synthetic methods to produce designed bimetallic nanoparticles with tailored active sites for improving catalysis. The first method explored uses the polymer polyvinylpyrrolidone as a capping agent while subsequent deposition techniques are employed to tailor the surface layer. The second method uses a mesoporous silica (SBA-15) which induces the surface segregation of some secondary metals. These two synthetic methods are evaluated through extensive characterisation to better understand the metallic interfaces and through the use of the formic acid decomposition reaction to understand the changes in the active sites at the surfaces. The SBA-15 method was also used to produce a series of catalysts with enhanced activity for the oxygen reduction reaction. The research presented is a step towards highly designed nanoparticle catalysts, with the tailoring of active sites made possible through degree of interaction of a secondary metal.